Neighbour and environmental influences on the growth patterns of two temperate Haliclonid sponges - Abdo, D.; McDonald, J.; Harvey, Euan; Fromont, J.; Kendrick, G. (CSIRO Publishing, 2008)
Understanding the growth dynamics of an organism is central to understanding its ecology and biology. Sponges often dominate many subtidal habitats, however, determining their growth dynamics is often difficult owing to the plastic and amorphous morphologies that occur in many species. Two sympatric Haliclonid sponge species were examined usinga novel photogrammetric technique to understand how environmental and competitive influences affect their growth. Sponges of both species were tagged and monitored over a 14-month period. Haliclona sp. 1 (green Haliclona) showed little variation in growth compared with Haliclona sp. 2 (brownHaliclona),which had a significant seasonal growth pattern.Both green and brown Haliclona grew a significant amount over the period of study (green Haliclona: 3.4% month-1; brown Haliclona: 6.0% month-1 (with neighbours) and 4.1% month-1 (without neighbours)). In both species, growth was not significantly influenced by competition from neighbours; rather, neighbouring organisms appeared to provide protection from adverse environmental conditions. The growth dynamics of both species have important implications for the maintenance of both species populations, particularly given the important habitat they provide for other organisms, and their potential exploitation for the supply of bioactive metabolites.